Black aortic valve and coronary arteries in liver transplantation patient: case report - S. Vancoillie; J. Roosen; C. Bourgain; H. Depraetere (The Cardiothoracic Surgeon, 2023)
Abstract Background Black pigmentation of the aortic valve and coronary arteries has been reported to be caused by alkaptonuria or minocycline. In patients with liver transplantation it has been described only once, after exposure to minocycline. We report a second case of such pigmentation in a liver transplantation patient, for whom none of the known causes are an adequate explanation for this pigmentation. Case presentation Our 56-year-old male patient showed a complex history of two liver transplantations and sleeve gastrectomy, and had neither alkaptonuria nor a history of minocycline intake. He underwent an urgent coronary bypass grafting and aortic valve replacement because of an acute coronary syndrome based on three-vessel disease and progressive aortic valve stenosis. During this procedure, the aortic valve and coronary arteries had black pigmentation. Conclusions There are causes – other than alkaptonuria and minocycline – that can induce a black pigmentation of the aortic valve and coronary arteries. In patients with a history of liver transplantation, alteration in (dys)functional liver parenchyma or administration of substances related to the procedure of liver transplantation are possible causes. Identifying these is important because they are potentially harmful as they may induce degenerative changes and functional impairment of the aortic valve and coronary arteries. Further research is needed, but proves to be difficult due to the rare nature of this condition.